(untitled) (Colombia Medica, 2011)
The mouth is the gateway to our body. It represents 10% of human body volume; however, importantfunctions rely on the mouth: eating, degustation,exploring the world as a child, chewing, digestion,tasting, biting, breathing through the mouth, vomiting,kissing, smiling, speaking, nonverbal communication,sex appeal, and social relations also depend on havinga healthy and functional mouth. The teeth, tongue,gums, nerves, muscles, ligaments, veins, arteries, bones,connective tissue, and epithelia are organized in thecomplex structural array that constitutes the mouth.The mouth establishes anatomical relationships withother essential organs like the pharynx, the esophagus,the nose, the face, the ears, the orbits and, perhaps mostimportant, the brain. The physiologic mouth boundarywith the body is by far more complex. Just to mentionthat saliva is an extremely important defensive bodyfluid, released into the mouth by which innate andacquired immune mechanisms effectively defend thehost against foreign insults. Saliva flow reduction inde-fectible results in increasing dental decay, periodontaldisease, and oral ulcers